2015
DOI: 10.1088/0004-637x/811/1/60
|View full text |Cite
|
Sign up to set email alerts
|

COLLISIONAL CASCADE CALCULATIONS FOR IRREGULAR SATELLITE SWARMS IN FOMALHAUT b

Abstract: We describe an extensive suite of numerical calculations for the collisional evolution of irregular satellite swarms around 1-300 M ⊕ planets orbiting at 120 AU in the Fomalhaut system. For 10-100 M ⊕ planets, swarms with initial masses of roughly 1% of the planet mass have cross-sectional areas comparable to the observed cross-sectional area of Fomalhaut b. Among 30-300 M ⊕ planets, our calculations yield optically thick swarms of satellites for ages of 1-10 Myr. Observations with HST and ground-based AO inst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 106 publications
(176 reference statements)
0
5
0
Order By: Relevance
“…This indicates supercomets would have seldom collided over the age of the system, and their size distribution would therefore have been set by growth processes during planet formation, where the latter is completely unconstrained observationally. In addition, if the extrapolation of the size distribution to these sizes were valid, the total mass of the belt (∼0.4 Jupiter masses) would be ∼4 times higher than the 29 M ⊕ that an initial minimum mass solar nebula (MMSN) planetesimal disk would have had between 120 and 150 AU (Kenyon & Bromley 2008).In general, these high belt masses required challenge the validity of our extrapolation, and point to a likely steeper size distribution for the large primordial bodies (as is the case for Kuiper belt objects, e.g. Schlichting et al 2013).…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates supercomets would have seldom collided over the age of the system, and their size distribution would therefore have been set by growth processes during planet formation, where the latter is completely unconstrained observationally. In addition, if the extrapolation of the size distribution to these sizes were valid, the total mass of the belt (∼0.4 Jupiter masses) would be ∼4 times higher than the 29 M ⊕ that an initial minimum mass solar nebula (MMSN) planetesimal disk would have had between 120 and 150 AU (Kenyon & Bromley 2008).In general, these high belt masses required challenge the validity of our extrapolation, and point to a likely steeper size distribution for the large primordial bodies (as is the case for Kuiper belt objects, e.g. Schlichting et al 2013).…”
Section: 2mentioning
confidence: 99%
“…The subsequent Hubble Space Telescope (HST) discovery of the very low mass companion Fomalhaut b (Kalas et al 2008) appeared consistent with the hypothesis that a planet could sculpt the inner edge (Quillen 2006;Chiang et al 2009), until further observations showed that Fomalhaut b's orbit is highly eccentric (Kalas et al 2013;Beust et al 2014;Pearce et al 2015). The existence of Fomalhaut b has been independently replicated (Currie et al 2012;Galicher et al 2013), but its physical properties continue to be investigated (Marengo et al 2009;Kennedy & Wyatt 2011;Janson et al 2012;Tamayo 2014;Kenyon et al 2014;Neuhäuser et al 2015;Kenyon & Bromley 2015;Lawler et al 2015;Janson et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Further, such outcomes might produce cascades which grind the debris into dust rather than orbitally perturbing it (Kenyon & Bromley 2017).…”
Section: Planets In Polluted Single White Dwarf Systemsmentioning
confidence: 99%
“…Ref. 20 found that satellite swarms around planets of mass 10 to 100 M Earth that have evolved for 100 to 400 My could match the properties of Fomalhaut b. Ref. 17 suggested that the object could consist of dust created in the collision of two modest-sized (50 km) planetesimals similar to members of the Kuiper Belt.…”
mentioning
confidence: 99%